An overview of statin-induced myopathy and perspectives for the future. Issue 5 (3rd May 2020) - Nikolic, Dragana; Banach, Maciej; Chianetta, Roberta; Luzzu, Luca Marco; Pantea Stoian, Anca; Diaconu, Camelia Cristina; Citarrella, Roberto; Montalto, Giuseppe; Rizzo, Manfredi
ABSTRACT: Introduction : Statins remain the most commonly prescribed lipid-lowering drug class for the treatment of atherosclerotic cardiovascular disease. Their well-recognized side effects are known as statin-associated muscle symptom (SAMS). Some advances in this field have been made in recent years, but the understanding of the mechanisms has lagged. Investigating the specific role of the anti-HMGCR autoantibody, pharmacokinetic genetic variants, characterization of the known phenotypes of statin toxicity, in relation to clinical markers of disease, is of high importance. Areas covered : We summarized currently available findings (on PubMed) related to SAMS and discussed the therapeutic approaches, risk factors, drug interactions, potential novel systems, algorithms and biomarkers for SAMS detection. CoQ10 supplementation has been suggested as a complementary approach to manage SAMS, while vitamin D levels may be useful for both the diagnosis and management. Expert Opinion/Commentary : Further studies might help to understand the easiest way to diagnose SAMS, suitable prevention and an effective non-statin therapy. This review sheds new light on the future directions in both research and clinical practice, which will help with rapid risk assessment, identification of the SAMS risk factors in order to decrease the incidence of statins' adverse effects, and the most effective therapy.